2009
DOI: 10.5172/conu.32.1-2.9
|View full text |Cite
|
Sign up to set email alerts
|

Nursing’s orphans: How the system of nursing education in Australia is undermining professional identity

Abstract: This paper draws on the results of a national study of approaches to teaching nursing's history in Australia. We argue that the neglect of history learning within undergraduate nursing and midwifery education is undermining the development in students of a strong professional nursing identity. The data in our study shows that instead of proud, informed professionals, we are at risk of producing a generation of professional orphans -- unaware of who they are and where they've come from, unaware of reasons under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…A weak social identity has been associated with a poor capacity for coping when under duress: a recent study found that junior doctors’ lower levels of self‐reported professional identity were significantly related to their higher levels of personal, patient‐related and work‐related burnout scores (and vice versa) 14 . Other implications of a weak professional identity include retention and teamwork problems 15 . Alternatively, the development of a strong positive professional identity can be beneficial to health care practice (eg, ethical decision making), and health care professionals’ career choice, wellbeing and life satisfaction 14 .…”
mentioning
confidence: 99%
“…A weak social identity has been associated with a poor capacity for coping when under duress: a recent study found that junior doctors’ lower levels of self‐reported professional identity were significantly related to their higher levels of personal, patient‐related and work‐related burnout scores (and vice versa) 14 . Other implications of a weak professional identity include retention and teamwork problems 15 . Alternatively, the development of a strong positive professional identity can be beneficial to health care practice (eg, ethical decision making), and health care professionals’ career choice, wellbeing and life satisfaction 14 .…”
mentioning
confidence: 99%
“…These nurses are/were productive, long-standing members of an Australian nursing community and each made significant contributions over the history of their career with most of them still practicing. Sharing their successes is important for building a cultural heritage (Madsen, McAllister, Godden, Greenhill, and Reed, 2009). These nurse leaders also convey a strong value system that seems inherent in effective leadership.…”
Section: Discussionmentioning
confidence: 98%
“…Mental health nursing, like nursing generally within Australia, seems largely unaware of its history; the events and practices that shaped its nuances and common sense beliefs (Madsen, McAllister, Godden, Greenhill, & Reed, 2009;. Without clarifying these aspects of our unique culture, we risk losing the struggle for purpose and autonomous identity, and consign for future generations of MHNs a subordinate, if not superfluous, role.…”
mentioning
confidence: 93%
“…"I do think that those of us that have been bitten by the scholarship bug -once you find out how interesting it is you find the time" (B:2). In these respects there was a developing recognition of one's identity as a scholar, adding to a sense of empowerment (Madsen, McAllister, Godden, Greenhill, & Reid, 2009) in their everday practice.…”
Section: Recognition Of Self As Scholarmentioning
confidence: 99%